Bringing an ecological view of change to Landsat‐based remote sensing. Issue 6 (18th June 2014) - Kennedy, Robert E; Andréfouët, Serge; Cohen, Warren B; Gómez, Cristina; Griffiths, Patrick; Hais, Martin; Healey, Sean P; Helmer, Eileen H; Hostert, Patrick; Lyons, Mitchell B; Meigs, Garrett W; Pflugmacher, Dirk; et al.
Abstract : When characterizing the processes that shape ecosystems, ecologists increasingly use the unique perspective offered by repeat observations of remotely sensed imagery. However, the concept of change embodied in much of the traditional remote‐sensing literature was primarily limited to capturing large or extreme changes occurring in natural systems, omitting many more subtle processes of interest to ecologists. Recent technical advances have led to a fundamental shift toward an ecological view of change. Although this conceptual shift began with coarser‐scale global imagery, it has now reached users of Landsat imagery, since these datasets have temporal and spatial characteristics appropriate to many ecological questions. We argue that this ecologically relevant perspective of change allows the novel characterization of important dynamic processes, including disturbances, long‐term trends, cyclical functions, and feedbacks, and that these improvements are already facilitating our understanding of critical driving forces, such as climate change, ecological interactions, and economic pressures.